Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Identification of the promoter region of the human P2RX7 gene - Luyao Liu; Yoshiteru Kagawa; Colin L. Masters; Stanley S. Stylli; Theo Mantamadiotis; Ben J. Gu (Purinergic Signalling, 2026)

Quantifying soil organic matter stock distribution and origin following over a century of maize-based cropping in the former tallgrass prairie region of central USA - Yuhei Nakayama; Michael D. Masters; Evan H. DeLucia; Andrew J. Margenot (Agriculture, Ecosystems & Environment, 2026)

Association of Sport Helmet Status on Concussion Presentation and Recovery in Male Collegiate Student-Athletes - Adrian J. Boltz; Landon B. Lempke; Reid A. Syrydiuk; Stefan Duma; Paul Pasquina; Thomas W. McAllister; Michael McCrea; Avinash Chandran; Steven P. Broglio; Louise Kelly; Justus Ortega; Nicholas Port; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Africa Alive Corridors: Transdisciplinary Research based on African Footprints - B. Linol; M. Doucouré; J. Anderson; F. Toteu; W. Miller; P. Vale; P. Hoffman; G. I. H. Kerley; R. Auerbach; C. Thiart; M. Meghraoui; N. Dhliwayo; et al. (Geoheritage, 2024)
The idea of Africa Alive Corridors (AAC) evolved from Gondwana geological mapping to a comprehensive, more inclusive and dynamic approach to transdisciplinary research known as Earth Stewardship Science. Twenty designated corridors explore the geo-biological and cultural heritage of different regions of Africa over various periods, from deep time to the Anthropocene. Each corridor reveals a specific lens through which to investigate some of the rich scientific narratives embedded within it. The concept also facilitates learning and knowledge exchange across numerous disciplines: archeology, geology, geophysics, oceanography, glaciology, biology, botany, ecology, agriculture, engineering, spatial statistics, social sciences, and the humanities. This contribution analyses ten selected corridors in southern and western Africa, the Congo Basin, East Africa, and Madagascar. The various research themes explored include Earth impact hazard, origins of humankind, Snowball Earth, coastal food systems and conservation, the biogeography of lemurs, human settlement dynamics in Cameroon, tectonically linked earthquake occurrences in Algeria and Morocco, modelling land-use changes in the Western Rift Valley, trades and civilizations of the Mali Empire, Mbira music, and contemporary art. The ongoing work on these—and ten other—corridors has considerable potential to host new international collaborations to develop the links between society and natural sciences in Africa. Ultimately, AAC will benefit all stakeholders, especially the youth, in understanding and responding to societal needs and current global challenges.

Constraints on mineral-associated and particulate organic carbon response to regenerative management: carbon inputs and saturation deficit - Alison E. King; Joseph P. Amsili; S. Carolina Córdova; Steve Culman; Steven J. Fonte; James Kotcon; Michael D. Masters; Kent McVay; Daniel C. Olk; Aaron M. Prairie; Meagan Schipanski; Sharon K. Schneider; et al. (Soil and Tillage Research, 2024)

Upscaling marine forest restoration: challenges, solutions and recommendations from the Green Gravel Action Group - Georgina Valentine Wood; Karen Filbee-Dexter; Melinda Ann Coleman; Jurgen Valckenaere; J. David Aguirre; Paige M. Bentley; Paul Carnell; Phoebe Damayanthi Dawkins; Lauren N. Dykman; Hannah S. Earp; Leeann B. Ennis; Prue Francis; et al. (Frontiers in Marine Science, 2024)
Introduction To counteract the rapid loss of marine forests globally and meet international commitments of the UN Decade on Ecosystem Restoration and the Convention on Biological Diversity ‘30 by 30’ targets, there is an urgent need to enhance our capacity for macroalgal restoration. The Green Gravel Action Group (GGAG) is a global network of 67 members that are working on the restoration of a diverse range of macroalgal forests and it aims to facilitate knowledge exchange to fast-track innovation and implementation of outplanting approaches worldwide. Methods Here, we overview 25 projects conducted by members of the group that are focused on testing and developing techniques for macroalgal restoration. Based on these projects, we summarise the major challenges associated with scaling up the area of marine forests restored. Results We identify several critical challenges that currently impede more widespread rollout of effective large-scale macroalgal restoration worldwide: 1) funding and capacity limitations, 2) difficulties arising from conditions at restoration sites, 3) technical barriers, and 4) challenges at the restoration-policy interface. Discussion Despite these challenges, there has been substantial progress, with an increasing number of efforts, community engagement and momentum towards scaling up activities in recent years. Drawing on the collective expertise of the GGAG, we outline key recommendations for the scaling up of restoration efforts to match the goals of international commitments. These include the establishment of novel pathways to fund macroalgal restoration activities, building skills and capacity, harnessing emerging innovations in mobile hatchery and seeding technologies, and the development of the scientific and governance frameworks necessary to implement and monitor macroalgal restoration projects at scale.

Intercomparison of surface velocimetry techniques for drone-based marine current characterization - Iain Fairley; Nicholas King; Jason McIlvenny; Matthew Lewis; Simon Neill; Benjamin J. Williamson; Ian Masters; Dominic E. Reeve (Estuarine, Coastal and Shelf Science, 2024)

Output of a tidal farm in yawed flow and varying turbulence using GAD-CFD - Charles E. Badoe; Xiaorong Li; Alison J. Williams; Ian Masters (Ocean Engineering, 2024)

Validating assumptions in calculating carbon dioxide removal by enhanced rock weathering in Kantola et al., 2023 - Adam Wolf; Elliot Chang; Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Alison Marklein; Caitlin E. Moore; Carl J. Bernacchi; Evan H. DeLucia (Global Change Biology, 2024)

Improved net carbon budgets in the US Midwest through direct measured impacts of enhanced weathering - Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Elliot Chang; Alison Marklein; Caitlin E. Moore; Adam von Haden; Carl J. Bernacchi; Adam Wolf; Dimitar Z. Epihov; David J. Beerling; Evan H. DeLucia (Global Change Biology, 2023)
Terrestrial enhanced weathering (EW) through the application of Mg‐ or Ca‐rich rock dust to soil is a negative emission technology with the potential to address impacts of climate change. The effectiveness of EW was tested over 4 years by spreading ground basalt (50 t ha −1 year −1 ) on maize/soybean and miscanthus cropping systems in the Midwest US. The major elements of the carbon budget were quantified through measurements of eddy covariance, soil carbon flux, and biomass. The movement of Mg and Ca to deep soil, released by weathering, balanced by a corresponding alkalinity flux, was used to measure the drawdown of CO 2 , where the release of cations from basalt was measured as the ratio of rare earth elements to base cations in the applied rock dust and in the surface soil. Basalt application stimulated peak biomass and net primary production in both cropping systems and caused a small but significant stimulation of soil respiration. Net ecosystem carbon balance (NECB) was strongly negative for maize/soybean (−199 to −453 g C m −2 year −1 ) indicating this system was losing carbon to the atmosphere. Average EW (102 g C m −2 year −1 ) offset carbon loss in the maize/soybean by 23%–42%. NECB of miscanthus was positive (63–129 g C m −2 year −1 ), indicating carbon gain in the system, and EW greatly increased inorganic carbon storage by an additional 234 g C m −2 year −1 . Our analysis indicates a co‐deployment of a perennial biofuel crop (miscanthus) with EW leads to major wins—increased harvested yields of 29%–42% with additional carbon dioxide removal (CDR) of 8.6 t CO 2 ha −1 year −1 . EW applied to maize/soybean drives a CDR of 3.7 t CO 2 ha −1 year −1 , which partially offsets well‐established carbon losses from soil from this crop rotation. EW applied in the US Midwest creates measurable improvements to the carbon budgets perennial bioenergy crops and conventional row crops.

Assessment of Nutrition Knowledge and Considerations Among Experienced Backpackers - K. Beaty; M. Masters; M. Battson; C. Turner; S. Schuster; S. Yuan; J. Salerno (Journal of the Academy of Nutrition and Dietetics, 2023)

Relationship Between Food Neophobia Levels and Self-reported Nutrient Intake in College Students - J. Lunsford; R. Sinley; M. Masters; E. Murray; R. Trammell (Journal of the Academy of Nutrition and Dietetics, 2023)

Prevalence of Food Insecurity and Association with Depression Among Graduate Students at an Urban University - K. Bell; A. Hollenbeck; M. Masters; J. Lunsford; L. Pollitt; K. Whitson; D. Mccutcheon (Journal of the Academy of Nutrition and Dietetics, 2023)

Discussion on “Stinging News: ‘Dickinsonia’ discovered in the Upper Vindhyan of India not worth the buzz” by Meert, et al. (2023) - Gregory J. Retallack; Sharad Master; Ranjit G. Khangar; Merajuddin Khan (Gondwana Research, 2023)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of a physical activity intervention on brain atrophy in older adults at risk of dementia: a randomized controlled trial - Benjamin Sinclair; Chris Steward; Vijay Venkatraman; Rowa Aljondi; Kay L. Cox; Kathryn A. Ellis; David Ames; Colin L. Masters; Pramit M. Phal; Matthew J. Sharman; Elizabeth V. Cyarto; Michelle M. Y. Lai; et al. (Brain Imaging and Behavior, 2021)

Commonality of adherent-invasive Escherichia coli isolated from patients with extraintestinal infections, healthy individuals and the environment - D. J. Astley; N. Masters; A. Kuballa; M. Katouli (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Effective Removal of Toxic Heavy Metal Ions from Aqueous Solution by CaCO3 Microparticles - Rui Zhang; Joseph J. Richardson; Anthony F. Masters; Gyeongwon Yun; Kang Liang; Thomas Maschmeyer (Water, Air, & Soil Pollution, 2018)

Root volume distribution of maturing perennial grasses revealed by correcting for minirhizotron surface effects - Christopher K. Black; Michael D. Masters; David S. LeBauer; Kristina J. Anderson-Teixeira; Evan H. DeLucia (Plant and Soil, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Agricultural policy for improved nutrition in Africa and Asia: evidence to guide the US Government’s investments in food security - William A. Masters; Brooke Colaiezzi; Katherine Dennison; Jeff Hill; Elizabeth Jordan-Bell; Ahmed Kablan; Melanie Thurber; Lorraine J. Weatherspoon; James Oehmke (Food Security, 2015)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

Debranching of soluble wheat arabinoxylan dramatically enhances recalcitrant binding to cellulose - Michael J. Selig; Lisbeth G. Thygesen; Claus Felby; Emma R. Master (Biotechnology Letters, 2015)

Neonatal body condition, immune responsiveness, and hematocrit predict longevity in a wild bird population - E. Keith Bowers; Christine J. Hodges; Anna M. Forsman; Laura A. Vogel; Brian S. Masters; Bonnie G. P. Johnson; L. Scott Johnson; Charles F. Thompson; Scott K. Sakaluk (Ecology, 2014)
Measures of body condition, immune function, and hematological health are widely used in ecological studies of vertebrate populations, predicated on the assumption that these traits are linked to fitness. However, compelling evidence that these traits actually predict long‐term survival and reproductive success among individuals in the wild is lacking. Here, we show that body condition (i.e., size‐adjusted body mass) and cutaneous immune responsiveness to phytohemagglutinin (PHA) injection among neonates positively predict recruitment and subsequent longevity in a wild, migratory population of House Wrens ( Troglodytes aedon ). However, neonates with intermediate hematocrit had the highest recruitment and longevity. Neonates with the highest PHA responsiveness and intermediate hematocrit prior to independence eventually produced the most offspring during their lifetime breeding on the study site. Importantly, the effects of PHA responsiveness and hematocrit were revealed while controlling for variation in body condition, sex, and environmental variation. Thus, our data demonstrate that body condition, cutaneous immune responsiveness, and hematocrit as a neonate are associated with individual fitness. Although hematocrit's effect is more complex than traditionally thought, our results suggest a previously underappreciated role for this trait in influencing survival in the wild.

Altered Belowground Carbon Cycling Following Land-Use Change to Perennial Bioenergy Crops - Kristina J. Anderson-Teixeira; Michael D. Masters; Christopher K. Black; Marcelo Zeri; Mir Zaman Hussain; Carl J. Bernacchi; Evan H. DeLucia (Ecosystems, 2013)

Prevalence of β-thalassemia and other haemoglobinopathies in six cities in India: a multicentre study - D. Mohanty; R. B. Colah; A. C. Gorakshakar; R. Z. Patel; D. C. Master; J. Mahanta; S. K. Sharma; U. Chaudhari; M. Ghosh; S. Das; R. P. Britt; S. Singh; et al. (Journal of Community Genetics, 2013)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

The structure of dopamine induced α-synuclein oligomers - Agata Rekas; Robert B. Knott; Anna Sokolova; Kevin J. Barnham; Keyla A. Perez; Colin L. Masters; Simon C. Drew; Roberto Cappai; Cyril C. Curtain; Chi L. L. Pham (European Biophysics Journal, 2010)

A Serial Analysis of Gene Expression Profile of the Alzheimer’s Disease Tg2576 Mouse Model - Amee J. George; Lavinia Gordon; Tim Beissbarth; Irene Koukoulas; R. M. Damian Holsinger; Victoria Perreau; Roberto Cappai; Seong-Seng Tan; Colin L. Masters; Hamish S. Scott; Qiao-Xin Li (Neurotoxicity Research, 2010)

Pragmatism and Practice in Classifying Threats: Reply to Balmford et al. - NICK SALAFSKY; STUART H.M. BUTCHART; DANIEL SALZER; ALISON J. STATTERSFIELD; RACHEL NEUGARTEN; CRAIG HILTON‐TAYLOR; BEN COLLEN; LAWRENCE L. MASTER; SHEILA O’CONNOR; DAVID WILKIE (Conservation Biology, 2009)

A Standard Lexicon for Biodiversity Conservation: Unified Classifications of Threats and Actions - NICK SALAFSKY; DANIEL SALZER; ALISON J. STATTERSFIELD; CRAIG HILTON‐TAYLOR; RACHEL NEUGARTEN; STUART H. M. BUTCHART; BEN COLLEN; NEIL COX; LAWRENCE L. MASTER; SHEILA O'CONNOR; DAVID WILKIE (Conservation Biology, 2008)
An essential foundation of any science is a standard lexicon. Any given conservation project can be described in terms of the biodiversity targets, direct threats, contributing factors at the project site, and the conservation actions that the project team is employing to change the situation. These common elements can be linked in a causal chain, which represents a theory of change about how the conservation actions are intended to bring about desired project outcomes. If project teams want to describe and share their work and learn from one another, they need a standard and precise lexicon to specifically describe each node along this chain. To date, there have been several independent efforts to develop standard classifications for the direct threats that affect biodiversity and the conservation actions required to counteract these threats. Recognizing that it is far more effective to have only one accepted global scheme, we merged these separate efforts into unified classifications of threats and actions, which we present here. Each classification is a hierarchical listing of terms and associated definitions. The classifications are comprehensive and exclusive at the upper levels of the hierarchy, expandable at the lower levels, and simple, consistent, and scalable at all levels. We tested these classifications by applying them post hoc to 1191 threatened bird species and 737 conservation projects. Almost all threats and actions could be assigned to the new classification systems, save for some cases lacking detailed information. Furthermore, the new classification systems provided an improved way of analyzing and comparing information across projects when compared with earlier systems. We believe that widespread adoption of these classifications will help practitioners more systematically identify threats and appropriate actions, managers to more efficiently set priorities and allocate resources, and most important, facilitate cross‐project learning and the development of a systematic science of conservation.

Linking climate change and species invasion: an illustration using insect herbivores - NICOLA L. WARD; GREGORY J. MASTERS (Global Change Biology, 2007)
Climate change and invasive species are two of the most important ecological issues facing the world today. Yet, to date these two factors have largely been viewed independently. In order to prevent large‐scale economic and environmental damage and as a first step towards predicting and preventing invasions, it is important to understand the factors affecting invasions. Here, we focus on insect herbivores and link the climate change and invasive research fields. We illustrate using existing published research that life history traits can be useful indicators of future invasive potential. However, climate change will also affect propagule pressure and the communities into which invaders will arrive. With the aid of a meta‐analysis we show that climate‐induced community changes are likely to increase niche‐availability in the future, further exacerbating the problem of invasive species. It is timely and important that further research linking these two important ecological threats is undertaken.

Summer drought alters plant‐mediated competition between foliar‐ and root‐feeding insects - JOANNA T. STALEY; SIMON R. MORTIMER; MICHAEL D. MORECROFT; VALERIE K. BROWN; GREGORY J. MASTERS (Global Change Biology, 2007)
Summer droughts are predicted to increase in severity and frequency in the United Kingdom, due to climate change. Few studies have addressed the impacts of drought on interactions between species, and the majority have focussed on increases in CO 2 concentration and changes in temperature. Here, the effect of experimental summer drought on the strength of the plant‐mediated interaction between leaf‐mining Stephensia brunnichella larvae and root‐chewing Agriotes larvae was investigated. Agriotes larvae reduced the abundance and performance of S. brunnichella feeding on a mutual host plant, Clinopodium vulgare , as well as the rate of parasitism of the leaf‐miner. The interaction did not, however, occur on plants subjected to a severe drought treatment, which were reduced in size. Changes to summer rainfall, due to climate change, may therefore reduce the occurrence of plant‐mediated interactions between insect herbivores.

ORIGINAL ARTICLE: Eyes wide shut: can hypometabolism really explain the primate colonization of Madagascar? - J. C. Masters; B. G. Lovegrove; M. J. De Wit (Journal of Biogeography, 2007)
Aim We investigate the hypothesis that it was the capacity for torpor or hibernation that enabled the lemuriforms (and possibly other mammal groups, e.g. tenrecs and rodents) to invade Madagascar by means of over‐water dispersal. Location Madagascar, East Africa and the Mozambique Channel. Methods We consider the body weights and life‐style features of living primate taxa that employ heterothermy. Using this information as a standard for comparison, we summarize the available information on the Palaeogene strepsirrhine radiation (i.e. members of the infraorder Adapiformes, the extinct sister‐taxon to the lemuriforms, as well as putative stem lemuriforms), particularly with respect to possible trends in body weight among early, middle and late Eocene adapiforms. We discuss Eocene climatic conditions in the northern hemisphere and Africa, and assess the likelihood of adaptations for heterothermy in adapiforms. Finally, we estimate the body weights of the common ancestors to the living Lemuriformes and Lemuroidea using the method of phylogenetically independent contrasts. Results The mean body weights estimated for the early, middle and late Eocene strepsirrhine faunas remain at approximately 2 kg, outside of the range of living primates using heterothermy. The adapiforms’ appearance coincided with the ‘initial Eocene thermal maximum’, an unusually hot period of global warming, and their demise corresponded with a major cooling event coincident with the appearance of ice sheets on Antarctica. They show no evidence of having evolved adaptations that allowed them to withstand climatic deterioration. The body weights of the ancestral lemuriform and ancestral lemuroid are of a similar order to the mean body weight estimated for the adapiforms, i.e. approximately 1.8 and 2.1 kg, respectively. Main conclusions The available evidence argues against the widespread use of heterothermy by adapiforms. The adapiform–lemuriform divergence may have been the result of the lemuriforms adapting to the drier and more seasonal environments that characterized the African Eocene, and this suite of adaptations may have included the use of heterothermy, but there is as yet no substantial evidence to confirm the presence of either group on the continent prior to c. 40 Ma. The estimated body weights of the common lemuriform and lemuroid ancestors are well outside the size range of living mammals that employ heterothermy. We conclude that the hypothesis that it was the ability to use heterothermy that enabled the strepsirrhines, and not the haplorhines, to invade Madagascar, is unlikely. Alternative explanations for this anomaly should be sought.

Species Richness and Patterns of Invasion in Plants, Birds, and Fishes in the United States* - Thomas J. Stohlgren; David Barnett; Curtis Flather; Pam Fuller; Bruce Peterjohn; John Kartesz; Lawrence L. Master (Biological Invasions, 2006)

Did lemurs have sweepstake tickets? An exploration of Simpson's model for the colonization of Madagascar by mammals - J. Stankiewicz; C. Thiart; J. C. Masters; M. J. de Wit (Journal of Biogeography, 2006)
Aim To investigate the validity of Simpson's model of sweepstakes dispersal, particularly as it applies to the colonization of Madagascar by African mammals. We chose lemurs as a classic case. Location The East African coast, the Mozambique Channel and Madagascar. Methods First, we investigated the assumptions underlying Simpson's statistical model as it relates to dispersal events. Second, we modelled the fate of a natural raft carrying one or several migrating mammals under a range of environmental conditions: in the absence of winds or currents, in the presence of winds and currents, and with and without a sail. Finally, we investigated the possibility of an animal being transported across the Mozambique Channel by an extreme climatic event like a tornado or a cyclone. Results Our investigations show that Simpson's assumptions are consistently violated when applied to scenarios of over‐water dispersal by mammals. We suggest that a simple binomial probability model is an inappropriate basis for extrapolating the likelihood of dispersal events. One possible alternative is to use a geometric probability model. Our estimates of current and wind trajectories show that the most likely fate for a raft emerging from an estuary on the east coast of Africa is to follow the Mozambique current and become beached back on the African coast. Given prevailing winds and currents, transport from Madagascar to Africa is very much more likely than the reverse process. Freak transport by means of a hurricane or tornado is even less likely than rafting for mammals. Main conclusions Our models suggest that the scenario of sweepstakes dispersal that currently enjoys wide support is not valid at either the theoretical or the applied level when applied to the hypothetical invasion of Madagascar by African mammals. Alternative explanations should be sought.

Community Associations of Chalk Grassland Leafhoppers (Hemiptera: Auchenorrhyncha): Conclusions for Habitat Conservation - Norbert Maczey; Greg J. Masters; John A. Hollier; Simon R. Mortimer; Valerie K. Brown (Journal of Insect Conservation, 2005)

Grassland Leafhoppers (Hemiptera: Auchenorrhyncha) as Indicators of Habitat Condition – A Comparison of between-site and between-year differences in Assemblage Composition - J. A. Hollier; N. Maczey; G. J. Masters; S. R. Mortimer (Journal of Insect Conservation, 2005)

The Consistency of Extinction Risk Classification Protocols - TRACEY J. REGAN; MARK A. BURGMAN; MICHAEL A. McCARTHY; LAWRENCE L. MASTER; DAVID A. KEITH; GEORGINA M. MACE; SANDY J. ANDELMAN (Conservation Biology, 2005)
Systematic protocols that use decision rules or scores are seen to improve consistency and transparency in classifying the conservation status of species. When applying these protocols, assessors are typically required to decide on estimates for attributes that are inherently uncertain. Input data and resulting classifications are usually treated as though they are exact and hence without operator error. We investigated the impact of data interpretation on the consistency of protocols of extinction risk classifications and diagnosed causes of discrepancies when they occurred. We tested three widely used systematic classification protocols employed by the World Conservation Union, NatureServe, and the Florida Fish and Wildlife Conservation Commission. We provided 18 assessors with identical information for 13 different species to infer estimates for each of the required parameters for the three protocols. The threat classification of several of the species varied from low risk to high risk, depending on who did the assessment. This occurred across the three protocols investigated. Assessors tended to agree on their placement of species in the highest (50–70%) and lowest risk categories (20–40%), but there was poor agreement on which species should be placed in the intermediate categories. Furthermore, the correspondence between the three classification methods was unpredictable, with large variation among assessors. These results highlight the importance of peer review and consensus among multiple assessors in species classifications and the need to be cautious with assessments carried out by a single assessor. Greater consistency among assessors requires wide use of training manuals and formal methods for estimating parameters that allow uncertainties to be represented, carried through chains of calculations, and reported transparently.

Regional-scale fluid flow and element mobility in Barrow’s metamorphic zones, Stonehaven, Scotland - R. L. Masters; J. J. Ague (Contributions to Mineralogy and Petrology, 2005)

Correlations among Extinction Risks Assessed by Different Systems of Threatened Species Categorization - JULIAN J. O'GRADY; MARK A. BURGMAN; DAVID A. KEITH; LAWRENCE L. MASTER; SANDY J. ANDELMAN; BARRY W. BROOK; GEOFFREY A. HAMMERSON; TRACEY REGAN; RICHARD FRANKHAM (Conservation Biology, 2004)
Many different systems are used to assess levels of threat faced by species. Prominent ones are those used by the World Conservation Union, NatureServe, and the Florida Game and Freshwater Fish Commission (now the Florida Fish and Wildlife Conservation Commission). These systems assign taxa a threat ranking by assessing their demographic and ecological characteristics. These threat rankings support the legislative protection of species and guide the placement of conservation programs in order of priority. It is not known, however, whether these assessment systems rank species in a similar order. To resolve this issue, we assessed 55 mainly vertebrate taxa with widely differing life histories under each of these systems and determined the rank correlations among them. Moderate, significant positive correlations were seen among the threat rankings provided by the three systems (correlations 0.58–0.69). Further, the threat rankings for taxa obtained using these systems were significantly correlated to their rankings based on predicted probability of extinction within 100 years as determined by population viability analysis (correlations 0.28–0.37). The different categorization systems, then, yield related but not identical threat rankings, and these rankings are associated with predicted extinction risk.

Protocols for listing threatened species can forecast extinction - David A. Keith; Michael A. McCarthy; Helen Regan; Tracey Regan; Christy Bowles; Claire Drill; Corey Craig; Belinda Pellow; Mark A. Burgman; Larry L. Master; Mary Ruckelshaus; Berin Mackenzie; et al. (Ecology Letters, 2004)
Risk‐ranking protocols are used widely to classify the conservation status of the world's species. Here we report on the first empirical assessment of their reliability by using a retrospective study of 18 pairs of bird and mammal species (one species extinct and the other extant) with eight different assessors. The performance of individual assessors varied substantially, but performance was improved by incorporating uncertainty in parameter estimates and consensus among the assessors. When this was done, the ranks from the protocols were consistent with the extinction outcome in 70–80% of pairs and there were mismatches in only 10–20% of cases. This performance was similar to the subjective judgements of the assessors after they had estimated the range and population parameters required by the protocols, and better than any single parameter. When used to inform subjective judgement, the protocols therefore offer a means of reducing unpredictable biases that may be associated with expert input and have the advantage of making the logic behind assessments explicit. We conclude that the protocols are useful for forecasting extinctions, although they are prone to some errors that have implications for conservation. Some level of error is to be expected, however, given the influence of chance on extinction. The performance of risk assessment protocols may be improved by providing training in the application of the protocols, incorporating uncertainty in parameter estimates and using consensus among multiple assessors, including some who are experts in the application of the protocols. Continued testing and refinement of the protocols may help to provide better absolute estimates of risk, particularly by re‐evaluating how the protocols accommodate missing data.

Iron inhibits neurotoxicity induced by trace copper and biological reductants - Anthony R. White; Kevin J. Barnham; Xudong Huang; Irene Voltakis; Konrad Beyreuther; Colin L. Masters; Robert A. Cherny; Ashley I. Bush; Roberto Cappai (JBIC Journal of Biological Inorganic Chemistry, 2004)

A method for the external attachment of miniature radio tags to pike Esox lucius - W. R. C. Beaumont; J. E. G. Masters (Fisheries Management and Ecology, 2003)

Methionine oxidation: Implications for the mechanism of toxicity of the β-amyloid peptide from Alzheimer's disease - Giuseppe D. Ciccotosto; Kevin J. Barnham; Robert A. Cherny; Colin L. Masters; Ashley I. Bush; Cyril C. Curtain; Roberto Cappai; Deborah Tew (International Journal of Peptide Research and Therapeutics, 2003)

Rare Species and the Use of Indicator Groups for Conservation Planning - Joshua J. Lawler; Denis White; Jean C. Sifneos; Lawrence L. Master (Conservation Biology, 2003)
Indicators of biodiversity have been proposed as a potential tool for selecting areas for conservation when information about species distributions is scarce. Although tests of the concept have produced varied results, sites selected to address indicator groups can include a high proportion of other species. We tested the hypothesis that species at risk of extinction are not likely to be included in sites selected to protect indicator groups. Using a reserve‐selection approach, we compared the ability of seven indicator groups—freshwater fish, birds, mammals, freshwater mussels, reptiles, amphibians, and at‐risk species of those six taxa—to provide protection for other species in general and at‐risk species in particular in the Middle Atlantic region of the United States. Although sites selected with single taxonomic indicator groups provided protection for between 61% and 82% of all other species, no taxonomic group provided protection for more than 58% of all other at‐risk species. The failure to cover at‐risk species is likely linked to their rarity. By examining the relationship between a species' probability of coverage by each indicator group and the extent of its geographic range within the study area, we found that species with more restricted ranges were less likely to be protected than more widespread species. Furthermore, we found that although sites selected with indicator groups composed primarily of terrestrial species ( birds and mammals ) included relatively high percentages of those species ( 82–85% ) they included smaller percentages of strictly aquatic species (27–55%). Finally, of both importance and possible utility, we found that at‐risk species themselves performed well as an indicator group, covering an average of 84% of all other species.

Copper Modulation of Ion Channels of PrP[106–126] Mutant Prion Peptide Fragments - J. I. Kourie; B. L. Kenna; D. Tew; M. F. Jobling; C. C. Curtain; C. L. Masters; K. J. Barnham; R. Cappai (The Journal of Membrane Biology, 2003)

A simple activity monitoring radio tag for fish - W. R. C. Beaumont; B. Cresswell; K. H. Hodder; J. E. G. Masters; J. S. Welton (Hydrobiologia, 2002)

Herbivory in global climate change research: direct effects of rising temperature on insect herbivores - Jeffery S. Bale; Gregory J. Masters; Ian D. Hodkinson; Caroline Awmack; T. Martijn Bezemer; Valerie K. Brown; Jennifer Butterfield; Alan Buse; John C. Coulson; John Farrar; John E. G. Good; Richard Harrington; et al. (Global Change Biology, 2002)
This review examines the direct effects of climate change on insect herbivores. Temperature is identified as the dominant abiotic factor directly affecting herbivorous insects. There is little evidence of any direct effects of CO 2 or UVB. Direct impacts of precipitation have been largely neglected in current research on climate change. Temperature directly affects development, survival, range and abundance. Species with a large geographical range will tend to be less affected. The main effect of temperature in temperate regions is to influence winter survival; at more northerly latitudes, higher temperatures extend the summer season, increasing the available thermal budget for growth and reproduction. Photoperiod is the dominant cue for the seasonal synchrony of temperate insects, but their thermal requirements may differ at different times of year. Interactions between photoperiod and temperature determine phenology; the two factors do not necessarily operate in tandem. Insect herbivores show a number of distinct life‐history strategies to exploit plants with different growth forms and strategies, which will be differentially affected by climate warming. There are still many challenges facing biologists in predicting and monitoring the impacts of climate change. Future research needs to consider insect herbivore phenotypic and genotypic flexibility, their responses to global change parameters operating in concert, and awareness that some patterns may only become apparent in the longer term.

Host-plant mediated effects of root herbivory on insect seed predators and their parasitoids - Gregory J. Masters; T. Hefin Jones; Matthew Rogers (Oecologia, 2001)

Introduction to Diversity and Speciation in the Prosimii - E. Zimmermann; J. Masters; Y. Rumpler (International Journal of Primatology, 2000)

Mitochondrial Sequences as Indicators of Genetic Classification in Bush Babies - M. DelPero; J. C. Masters; D. Zuccon; P. Cervella; S. Crovella; G. Ardito (International Journal of Primatology, 2000)

Host utilization and seasonal occurrence of Dermacentor - Thomas M. Kollars; James H. Oliver; Edwin J. Masters; Peggy G. Kollars; Lance A. Durden (Experimental and Applied Acarology, 2000)

Direct and indirect effects of climate change on St John's wort, Hypericum perforatum L. (Hypericaceae) - Laurel R. Fox; Sérvio P. Ribeiro; Valerie K. Brown; Gregory J. Masters; Ian P. Clarke (Oecologia, 1999)

Plant community dynamics in a calcareous grassland under climate change manipulations - Marcelo Sternberg; Valerie K. Brown; Gregory J. Masters; Ian P. Clarke (Plant Ecology, 1999)

The synthesis and spectroscopic analysis of the neurotoxic prion peptide 106–126: Comparative use of manual Boc and Fmoc chemistry - Michael F. Jobling; Colin J. Barrow; Anthony R. White; Colin L. Masters; Steven J. Collins; Roberto Cappai (International Journal of Peptide Research and Therapeutics, 1999)

Liposphere Local Anesthetic Timed-Release for Perineural Site Application - David B. Masters; Abraham J. Domb (Pharmaceutical Research, 1998)

Relationships between NADPH diaphorase staining and neuronal, endothelial, and inducible nitric oxide synthase and cytochrome P450 reductase immunoreactivities in guinea-pig tissues - H. M. Young; Anna J. O'Brien; John B. Furness; Daniela Ciampoli; James P. Hardwick; Timothy J. McCabe; Ramani Narayanasami; Bettie Sue S. Masters; W. Ross Tracey (Histochemistry and Cell Biology, 1997)

Seed Orchard Pest Management: The Case for Forest Service R&D - G. R. Hodge; C. J. Masters; R. S. Cameron; W. J. Lowe; R. J. Weir (Journal of Forestry, 1997)

Acute impact of an organophosphorus insecticide on microbes and small invertebrates of a mangrove estuary - S. Y. Newell; K. E. Cooksey; J. W. Fell; I. M. Master; C. Miller; M. A. Walter (Archives of Environmental Contamination and Toxicology, 1981)

Genetic control and ontogeny of microbody enzymes: A review - Roger S. Holmes; Colin J. Masters (Biochemical Genetics, 1978)

Enhancement of immunizing potency of a foot-and-mouth disease vaccine for cattle by treatment of the antigen with formaldehyde - G. N. Mowat; R. C. Masters; M. J. Prince (Archives of Virology, 1973)